Uma interface de programação distribuída para aplicações em otimização combinatória - Dantas, Allberson Bruno de Oliveira (2011)
This work was motivated by the need of exploiting the potential of distributed paralelism in combinatorial optimization applications. propose a distributed programming interface, To achieve this goal, we in which we cherish two main requirements: e ciency and reuse. The rst stems from the need of HPC (High applications require maximum possible performance. Performance Computing) Therefore, we specify our interface as an extension of the MPI library, which is assumed to be e cient for distributed applications. The reuse requirement must make compatible two important features: asynchronism and collective operations. Asynchronism must be present at our interface, once most of combinatorial optimization applications have an asynchronous nature. Collective operations are features that should be available in the interface, so that they can be used by applications in their execution. In order reach the reuse requirement, we based this interface on the Event- and Pulse-driven Models of Distributed Computing, once they are asynchronous and allow the incorporation of collective operations. We implemented partially the interface de ned in this work. In order to validate the use of the inteface by combinatorial optimization applications, we selected two applications and implemented them using our interface. They are the Branch-and-Bound technique and the Maximum Stable Set Problem (MSSP). We also provide some experimental results.